2018
DOI: 10.1093/toxsci/kfy080
|View full text |Cite|
|
Sign up to set email alerts
|

Role of TGFβ Signaling in Maternal Ethanol-Induced Fetal Articular Cartilage Dysplasia and Adult Onset of Osteoarthritis in Male Rats

Abstract: Based on our previous findings that prenatal ethanol exposure in offspring increased susceptibility to adult osteoarthritis, this study aimed to further investigate the direct toxicity of ethanol on fetal articular cartilage development. Rat bone marrow-derived stroma cells were capsulated in alginate beads, incubated in a chondrogenic differentiation medium, and cultured for 4 weeks with ethanol treatment at concentrations of 0, 4, 20, and 100 mM. Pregnant rats were treated with ethanol (4 g/kg/day) from gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Interestingly, in this study, we also found that PEE can cause dysplasia of articular cartilage, which shares a common tissue source with transitional cartilage. The theory that adult OA has intrauterine origin was rst proposed and proven by our previous research (Chen et al 2019a;Li et al 2020;Ni et al 2015a;Ni et al 2018;Ni et al 2015b;Pan et al 2016;Tie et al 2016a;Tie et al 2016b). In this study, we dynamically observed the effects of ethanol on articular cartilage development in fetuses at three time points: arthrogenesis (GD14), articular chondrogenesis (GD17) and just before birth (GD20).…”
Section: Articular Cartilage Dysplasia In Pee Offspring Originated From the Second Trimestermentioning
confidence: 80%
“…Interestingly, in this study, we also found that PEE can cause dysplasia of articular cartilage, which shares a common tissue source with transitional cartilage. The theory that adult OA has intrauterine origin was rst proposed and proven by our previous research (Chen et al 2019a;Li et al 2020;Ni et al 2015a;Ni et al 2018;Ni et al 2015b;Pan et al 2016;Tie et al 2016a;Tie et al 2016b). In this study, we dynamically observed the effects of ethanol on articular cartilage development in fetuses at three time points: arthrogenesis (GD14), articular chondrogenesis (GD17) and just before birth (GD20).…”
Section: Articular Cartilage Dysplasia In Pee Offspring Originated From the Second Trimestermentioning
confidence: 80%
“…TGF-β3 and SOX-9 are the main indicators of activation of the TGF-β superfamily of signaling pathways (32). SOX-9 is regulated and controlled by the TGF-β superfamily signaling pathway and serves as the main indicator of downstream signal transmission (33). Areas of positive staining for TGF-β3 in the groups without oral administration of naringin were relatively weak ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The tibias were sectioned sagittally at a thickness of 5 μm. Safranin O/fast green staining and hematoxylin-eosin (H&E) staining were performed by standard procedures [10]. The photo images of histology were captured using the Nikon NIS Elements BR light microscope (Nikon, Tokyo, Japan).…”
Section: Histological Assaysmentioning
confidence: 99%